Hydrothermal iron flux variability following rapid sea level changes. Issue 8 (25th April 2016) - Middleton, Jennifer L.; Langmuir, Charles H.; Mukhopadhyay, Sujoy; McManus, Jerry F.; Mitrovica, Jerry X.
Abstract: Sea level changes associated with Pleistocene glacial cycles have been hypothesized to modulate melt production and hydrothermal activity at ocean ridges, yet little is known about fluctuations in hydrothermal circulation on time scales longer than a few millennia. We present a high‐resolution record of hydrothermal activity over the past 50 ka using elemental flux data from a new sediment core from the Mir zone of the TAG hydrothermal field at 26°N on the Mid‐Atlantic Ridge. Mir sediments reveal sixfold to eightfold increases in hydrothermal iron and copper deposition during the Last Glacial Maximum, followed by a rapid decline during the sea level rise associated with deglaciation. Our results, along with previous observations from Pacific and Atlantic spreading centers, indicate that rapid sea level changes influence hydrothermal output on mid‐ocean ridges. Thus, climate variability may discretize volcanic processing of the solid Earth on millennial time scales and subsequently stimulate variability in biogeochemical interactions with volcanic systems. Key Points: New TAG sediment core used to examine hydrothermal response to sea level change Hydrothermal Fe and Cu deposition peak during Last Glacial Maximum and decline during deglaciation Global hydrothermal Fe flux and subsequent carbon export may vary across glacial cycles